Dukungan Sosial pada Survivor Kanker di Medan - Kenrick Chang; Meilisia Tri Gunawan; Elvy Grashiella; Hendra Jaya; Kenny William; Winida Marpaung (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The purpose of this research is to see how social support helps to cure cancer survivors. The source of this study consists of three research subjects who are a cancer survivor and three research informants. The sample selection used is the snowball sampling method. Research data are collected using natural observation methods and in-depth interview which are then arranged in verbatim form. The results shows that from the forms of social support, including emotional support, tangiable support, informational support, and companionship support, the most prominent is emotional support and with the existence of social supports, cancer sufferers can gain more confident andfeel more motivated to recover from cancer.